2017
DOI: 10.3847/1538-4357/836/1/8
|View full text |Cite
|
Sign up to set email alerts
|

ALMA Observations Show Major Mergers Among the Host Galaxies of Fast-growing, High-redshift, Supermassive Black Holes

Abstract: We present new ALMA band-7 data for a sample of six luminous quasars at  z 4.8, powered by fast-growing supermassive black holes (SMBHs) with rather uniform properties: the typical accretion rates and black hole masses are. Our sample consists of three "FIR-bright" sources, which were individually detected in previous Herschel/SPIRE observations, with star formation rates of C II -based dynamical mass estimates for the interacting SMGs are within a factor of ∼3 of the quasar hosts' masses, while the continuum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
120
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(147 citation statements)
references
References 157 publications
(260 reference statements)
27
120
0
Order By: Relevance
“…This is in agreement with previous studies of high-redshift quasars, which found that the broad UV emission lines of quasars tend to be blueshifted by several hundreds of km s −1 compared to emission lines probing the interstellar medium of the host galaxies, such as the [C ii] and CO lines (e.g. Riechers 2011;Willott et al 2015;Venemans et al 2016;Trakhtenbrot et al 2017;Decarli et al 2018).…”
Section: Co(5-4) and Co(8-7) Line Emissionsupporting
confidence: 93%
“…This is in agreement with previous studies of high-redshift quasars, which found that the broad UV emission lines of quasars tend to be blueshifted by several hundreds of km s −1 compared to emission lines probing the interstellar medium of the host galaxies, such as the [C ii] and CO lines (e.g. Riechers 2011;Willott et al 2015;Venemans et al 2016;Trakhtenbrot et al 2017;Decarli et al 2018).…”
Section: Co(5-4) and Co(8-7) Line Emissionsupporting
confidence: 93%
“…Here, it is striking to see that luminous QSOs reveal an excess in the number counts of massive star-forming galaxies in their vicinity at z > 6 ) and z ∼ 4.8 (Trakhtenbrot et al 2017). This is in agreement with the notion of a strongly clustered galaxy environment around QSOs at high redshifts (e.g., García-Vergara et al 2017) and an excess of unobscured dual AGN with <40 kpc separations (Hennawi et al 2006).…”
Section: Discussionsupporting
confidence: 75%
“…E.g. at z = 4.8, 50% of quasar host galaxies (3 out of 6) analysed by Trakhtenbrot et al (2017) are found to have companion submillimetre galaxies.…”
Section: Black Hole Environmentmentioning
confidence: 98%